Interoceanic Sex‐Biased Migration in Bluefish. Issue 5 (30th August 2014) - Miralles, L.; Juanes, F.; Garcia‐Vazquez, E.
Abstract: The Bluefish Pomatomus saltatrix is a highly migratory species that is composed of different stocks and populations along its nearly cosmopolitan distribution. The Bluefish is the only member of its genus and family, and high migration rates could prevent vicariant speciation across its wide geographical distribution. However, the extent of gene flow between distant populations is unknown. We employed two mitochondrial genes (cytochrome‐ c oxidase subunit I and cytochrome b ) and eight nuclear microsatellite loci to study population structure and infer dispersal of this important commercial and recreational fish across its Northern Hemisphere distribution. Higher gene flow estimates for nuclear loci (of biparental inheritance) than for mitochondrial loci (of maternal inheritance) suggested sex‐biased dispersal, which could be explained by greater female homing or fidelity to spawning sites and greater dispersal of males. Males could contribute more to transoceanic connectivity of Bluefish populations in the North Atlantic Ocean, thus shaping the observed pattern of spatial genetic structure of the Bluefish in its Northern Hemisphere distribution. Received February 1, 2014; accepted June 9, 2014